2006
DOI: 10.1097/01.mph.0000198269.61948.90
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Methylenetetrahydrofolate Reductase and Reduced Folate Carrier 1 Polymorphisms on High-Dose Methotrexate-Induced Toxicities in Children With Acute Lymphoblastic Leukemia or Lymphoma

Abstract: The authors investigated whether high-dose methotrexate-induced toxicity differed according to the presence of methylenetetrahydrofolate reductase (MTHFR) or reduced folate carrier 1 (RFC1) genetic polymorphism. The authors studied 15 children with acute lymphoblastic leukemia or lymphoblastic lymphoma who were treated using protocols that included high-dose methotrexate (3.0 g/m), for an overall total of 43 courses. Methotrexate-induced toxicities and the plasma methotrexate concentrations were evaluated retr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
58
2
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(69 citation statements)
references
References 23 publications
7
58
2
2
Order By: Relevance
“…Some other authors confirmed the above analysis in recent studies [45,75]. In contrast with above results, some other authors did not find any association between MTHFR and MTX-related toxicity or other side effects [22,26,27,31,35,73,76]. MTHFR polymorphisms may associate with MTX dosage.…”
Section: Methylenetetrahydrofolate Reductasecontrasting
confidence: 55%
See 1 more Smart Citation
“…Some other authors confirmed the above analysis in recent studies [45,75]. In contrast with above results, some other authors did not find any association between MTHFR and MTX-related toxicity or other side effects [22,26,27,31,35,73,76]. MTHFR polymorphisms may associate with MTX dosage.…”
Section: Methylenetetrahydrofolate Reductasecontrasting
confidence: 55%
“…In a study by Shimasaki et al [31], although they did not find any association between G80A polymorphism and MTX plasma concentration, vomiting episodes of grade 2 or worse were more frequently in G allele.…”
Section: Transporter Gene Polymorphisms Genetic Variations In Intake mentioning
confidence: 96%
“…The 80G>A SNP was also associated with methothexate bioavailability in the treatment of rheumatoid arthritis [119]. In other studies, however, no significant differences in methothexate uptake rates or toxicities were found between leukemia blast cells from ALL patients with the 80G and those with the 80A allele [120,121]. Pharmacogenetic studies investigating several targets of folate-related drugs have been recently reviewed and no clear evidence for the involvement of several known SLC19A1 polymorphisms [122].…”
Section: Pharmacogenetics Of Slc Transportersmentioning
confidence: 97%
“…. Unfortunately, MTX therapy may lead to myelosuppression, acute liver toxicity, nephrotoxicity, mucositis, and neurotoxicity [4,[6][7][8][9][10][11].MTX-associated toxicity is associated with several factors including dose, the duration of administration, patient risk factors, and genetic factors [12,13]. There are no sufficient data involving the use of HDMTX pharmacokinetic and toxicity information to anticipate hematologic toxicity in children with ALL.…”
Section: High-dose Methotrexate (Hdmtx) Chemotherapy With Leucovorin mentioning
confidence: 99%